The Binding Authority of DSN-MUI Fatwas in the National Legal System: An Analysis from the Perspective of Islamic Law and Legislative Theory - Abdullah Lawang, Karimuddin; Zulfikri, Zulfikri; Peristiwo, Hadi; Hanuddin, La; Nurdin, Nurdianasari; Habib, Muhamad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The National Sharia Council of the Indonesian Ulema Council (DSN-MUI) plays a central role in shaping the principles of Islamic economic law in Indonesia through its fatwas. These fatwas serve as primary references in the practices of Islamic financial institutions. However, the legal status of DSN-MUI fatwas within national legislation remains a subject of debate, particularly regarding their binding authority. This article aims to analyze the position of DSN-MUI fatwas from the perspective of Islamic law and legislative theory within the national legal system. This study employs a qualitative method with a normative and literature-based approach, examining various legal regulations and legal theories. The findings indicate that in Islamic law, fatwas are not absolutely binding unless institutionalized by an official authority. In the national context, DSN-MUI fatwas attain functional binding power as they are used as references in regulatory frameworks by Bank Indonesia, the Financial Services Authority (OJK), and Islamic financial institutions. Although these fatwas do not possess formal legal authority within the hierarchy of national legislation, they have become part of the living law that is internalized in national economic legal practices. Therefore, normative reinforcement is needed through explicit recognition in sectoral regulations to prevent legal vacuums. This study recommends the codification of DSN-MUI fatwas into derivative regulations to enhance their juridical legitimacy in supporting a just and legally certain Islamic economic legal system.